(untitled) (Al-Academy, 2024)
This study has came as a result to discover on the references of the educational theories which leads the professors in the educational art departments in the Iraqi universities through knowing these ideological references indeed in an important slice of the society. This slice is: the members of professoriate. The study goal knows the ideological references to these theories for the professors in these departments. In order to approve the research’s goals. The researcher has selected a sample contains (50) professoriate members in these departments in the Iraqi universities which they have the educational art profession among the next scientific degrees (assistant teacher. teacher. assistant professor & professor). The researcher has prepared a questionnaire which contains about (165) elements which represents the basic scientific & philosophic to each theory. These theories has been divided into 4 directions are (the behavioral. cognitive. human & social sides). This tool has been confirmed & it’s firm stability by the suitable statistical methods. Then the questionnaire’s in its’ final images true & special according to things what hold it from. The tool is stable. The connection agent was (0.86) by using the re-stability method. And after the researcher has confirmed from the reality from both of tool & subjectivity. It’s putting into effect on the selected sample from the professoriate in this college’s department to show the next:1. The theories (behavioral. human & social) hasn’t be accepted as a usual references between the professoriates’ in these departments. 2. these mentionedtheories according to the average as the next: A-the cognitive Attitude B- the social Attitude C-The behavioral Attitude D-The human AttitudeAccording to these results. The researcher has arrives to some conclusions which they are:1. There isn’t any existence to any clear & defined reference taken by each one of the professoriates. It’s a normal result for this art doesn’t having any educational clear & defines philosophy. 2. The cognitive side’s appearance to these theories in the 1st place returns to the associated features to this direction with the general directions to the art education. This makes it the strong candidate chosen by the teacher as an ideological to guide it ideas. 3. The mutual approach of the arithmetic mean presents clear evidence on what we living today as a state of conflict between the ideological prevalent currents in the educational mediums & not depending on a defined & clear philosophy which can put the society inside it. The researcher has recommended according to the results of his research which they are:1. Taking to account on build the statics of the art education to study the theories of educating in departments of this art. 2. present to each member who joins the teaching carrier in the university either as a lecturer or who’s selected as a member of professoriate the (trend) subject in the education theories in order to knowing what this theories & educational schools from conceptions & a different methods. 3. Hold a conference or a symposium which all the educational & scientific directions specialized in this branch in order to make imagination to an educational clear philosophy based on the fact which helps us to fact what we’re dreaming from teaching this profession. The researcher has introduced some kind of Suggestions:1. Made a similar study on the member of the professoriate with change the tool. And it prefers to take the note facing in the information collecting. 2. Make another study about the educational directed philosophy to the performance of the professoriate in the the art education departments and comparing them with another countries which has advanced in this profession. 3. Make a study about the references of the education theories in both of teachers & professors of the art education departments in both of the primary & secondary schools to know the effect’s level by the characters of the professors which they’ve been prepared by them during their preparation period.